THE CONTRIBUTION OF NURSES IN THE PREVENTION OF DISEASES REGARDING USE OF RURAL WORKERS BY AGROCHEMICAL - Maria José E Daher; Caroline Barbosa Angelim; Leonara Leite Vidal; Gracy Kelly Paes (Revista de Pesquisa Cuidado é Fundamental Online)
Resumo